Analisis Pengelolaan Keuangan Desa di Desa Pong Majok Kecamatan Lembor Kabupaten Manggarai Barat - Jehaman, Kristoforus; Harahap, Dea Arme Tiara; Wahyudi, Agus (CV. Kurnia Grup, 2024)
This research aims to determine and analyze village financial management carried out in Pong Majok Village. The research method used is a descriptive qualitative method using data collection techniques in the form of interviews and documentation. The research results show that village financial management in Pong Majok Village, Lembor District, West Manggari Regency includes planning village financial management, implementing village financial management, administering village financial management, reporting village financial management and accountability for village financial management. The financial management of Pong Majok Village, Lembor District is largely in accordance with Minister of Home Affairs regulations Number 20 of 2018 concerning Village Financial Management. However, there are still 3 (three) things that must be considered and re-evaluated by the Pong Majok Village government regarding the submission of monthly reports, the completeness of the attachment to the APBDesa accountability report and the submission of the APBDesa accountability report to the Pong Majok Village community.